Azathioprine in Autoimmune Pancreatitis: An Italian Experience - Amodio, Antonio; Frulloni, Luca; De Marchi, Giulia; Vitali, Francesco; Tumelero, Tiziana; Gabbrielli, Armando; Benini, Luigi; Vantini, Italo (JOP. Journal of the Pancreas, 2012)
Context Steroids are effective to induce remission in autoimmune pancreatitis (AIP). Low dosages of steroids are currently used as maintenance treatment in Japan. Immunosuppressive drugs have been suggested for maintenance treatment but no studies have been published yet for indications and their efficacy. Objective To evaluate the indications and the efficacy of azathioprine (AZA) for the long-term treatment of AIP. Patients and Methods All non operated AIP patients observed from 2003 were retrospectively evaluated. We excluded patients where AZA was used for the associated autoimmune disease. We divided patients in those not treated (AZA-) and treated (AZA+) with AZA at dosage of 2 mg/kg/day. Clinical, radiological and biochemical data were compared in AZA- and AZA+ groups and before and after AZA treatment. Pancreatic enlargement was considered as relapse of AIP. Results Fifty-eight patients (39 M, 19 F; age at clinical onset 45.8±17.1 years) were evaluated: 41 in AZA- and 17 in AZA+ groups. Older age, jaundice at clinical onset, number of relapse, high serum levels of IgG4, other organ’s involvement were significantly more frequently observed in AZA+ compared to AZA-. In AZA+ group, relapse was observed in 16/17 (94%) before treatment and in 2/16 (12%) after treatment (mean follow-up 3 years; range 1-8 years). Both AZA+ relapsing patients were treated with steroids, continuing AZA, and fully responded to therapy. One patient discontinued AZA for side effects (hepatitis). Conclusion AZA seems to be an effective and safe treatment in AIP.